Crisis and post-crisis urban gardening initiatives from a Southern European perspective: The case of Barcelona. (January 2019) - Calvet-Mir, Laura; March, Hug
Throughout the 20th century, urban gardening in central and northern Europe as well as in North America has received a great deal of academic attention. However, the recent proliferation of urban gardening in other geographies, such as southern Europe in the aftermath of the economic crisis of 2007–2008, remains underexplored. The economic crisis put on hold urban developments in many southern European cities, leaving idle plots of land waiting to be urbanized. The crisis also triggered radical political demands, such as those of the Indignados, as well as fuelling narratives revolving around social entrepreneurship and social innovation. Barcelona emerges as a laboratory of urban gardening initiatives in vacant lots mobilizing either radical urban demands or embedding new post-crisis rhetoric around social entrepreneurship. Through a combination of qualitative methods, including participant observation, a literature review, semi-structured interviews, informal conversations and field diaries, we present a characterization and evolution of the three most prominent urban gardening initiatives in the city of Barcelona (including 54 gardens at the end of 2016): the Network of Municipal Gardens (municipally led gardens for retired people); the Network of Communitarian Gardens (social movements); and the Empty Plots Plan (social entrepreneurial urban gardening). Subsequently, we discuss the different meanings of gardening in crisis/post-crisis Barcelona as well as the urban politics that each initiative articulates. Our results show that urban gardens within the city are an expression of different and non-exclusive meanings that explicitly or implicitly, in a context of crisis and post-crisis, mobilize notions of political gardening.